2016
DOI: 10.1007/s00330-016-4663-1
|View full text |Cite
|
Sign up to set email alerts
|

T2-weighted MRI-derived textural features reflect prostate cancer aggressiveness: preliminary results

Abstract: • T2W MRI-derived textural features correlate significantly with Gleason score and ADC. • T2W MRI-derived textural features differentiate Gleason score 3+4 from 4+3 cancers. • T2W image textural features could augment tumour characterization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
85
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(89 citation statements)
references
References 50 publications
4
85
0
Order By: Relevance
“…In recent years a number of studies have used a radiomics approach for the assessment for aggressiveness in prostatic carcinoma . These studies have demonstrated the feasibility of radiomics features for characterizing PCa habitats, where the mp‐MRI platform consisting of T 2 WI, DWI, and/or DCE was exploited in differentiating between Gleason score (GS) 3 + 4 and GS 4 + 3, reflecting cancer aggressiveness with a higher accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years a number of studies have used a radiomics approach for the assessment for aggressiveness in prostatic carcinoma . These studies have demonstrated the feasibility of radiomics features for characterizing PCa habitats, where the mp‐MRI platform consisting of T 2 WI, DWI, and/or DCE was exploited in differentiating between Gleason score (GS) 3 + 4 and GS 4 + 3, reflecting cancer aggressiveness with a higher accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many studies have applied the emerging radiomics technique to improve the diagnostic or predictive performance of PCa research . As an extension of texture analysis, radiomics enable medical images to be converted into high‐dimensional, mineable, and quantitative features by using high‐throughput extraction algorithms of these characterizations .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Accurate classification of the different Gleason score patterns on MRI is still a challenge and requires objective, reproducible, quantitative analysis methods. Texture analysis, which is a promising technique, could potentially distinguish between these different PCa patterns [5].…”
Section: Advances In Mrimentioning
confidence: 99%
“…These features are tested against a multitude of different genomic variables. Metrics, such as the false discovery rate, are often implemented to identify meaningful prospective variables in the setting of multiple hypotheses testing . A different exploratory method is hierarchical clustering, which is used to identify similarities in large genetic datasets.…”
Section: Introduction To Radiogenomicsmentioning
confidence: 99%